CaVa: An example of the automatic generation of virtual learning spaces - Martini, Ricardo (2018)
In order to construct web Learning Spaces (LS), more than collect and digitalize information, a powerful data extraction and querying engine and a sophisticated web publishing mechanism are needed. In this paper, a system to automatically construct those learning spaces based on a digital repository is presented. The system takes XML files from repositories and populates an ontology (representing the knowledge base, the core of our system) to create the triples internal representation. A Domain Specific Language (CaVaDSL) will be used to specify the learning spaces based on that ontology. The formal description, written in that DSL, will be processed by Cavagen engine to generate the final LS.